Can body shape index indicate obesity-associated inflammation and cardiovascular diseases in stage 3-4 chronic kidney disease patients? - Sasak, Gulsah; Basok, Banu Isbilen; Basci, Semih; Kocanoglu, Abdulkadir; Bakan, Ali; Isman, Ferruh Kemal (Ukrainian Journal of Nephrology and Dialysis, 2021)
The incidence and prevalence of obesity are increasing rapidly throughout the world. Various methods have been developed to evaluate obesity. A body shape index (aBSI) is based on waist circumference adjusted for height and weight. High BSI values have been found to be associated with early mortality. It is known that obesity is associated with inflammation and cardiovascular diseases. In this study, we examined the relationship between aBSI, inflammatory markers such as C-reactive protein and interleukin-6 and cardiovascular disease in patients with stage 3-4 chronic kidney disease. Methods. One hundred twenty patients were enrolled in this cross-sectional observational study. The mean aBSI value was 0.0870. Patients were divided into 2 groups according to the mean value of aBSI as there is no currently defined cut-off value for BSI. Those with aBSI ≤ 0.087 were allocated to group I, and those with aBSI> 0.0870 to group II. Results. Patients in group II had more cardiovascular disease than in group I. In partial Spearman correlation analysis, the presence of cardiovascular disease was correlated with aBSI (r = 0.36, p = 0.0001). aBSI higher than 0.0986 predicted cardiovascular disease in our cohort: the area under the curve (CI 95%) for aBSI was 0.715 (0.602-0.829). Conclusions. The relationship between aBSI and inflammation could not be shown. But we found that high aBSI is associated with increased cardiovascular disease. Further studies are needed to recommend the routine clinical use of aBSI as a cardiovascular disease marker.